An approach for Temporal Argumentation Using Labeled Defeasible Logic Programming (l-DeLP) - Maximiliano Celmo David Budán (Journal of Computer Science and Technology, 2012)
In the last decade, several argument-based formalisms have emerged, with application in many areas, such as legal reasoning, autonomous agents and multi-agent systems; many are based on Dung’s seminal work characterizing Abstract Argumentation Frameworks (AF). Recent research in the area has led to Temporal Argumentation Frameworks (TAF), that extend AF by considering the temporal availability of arguments. On the other hand, different more concrete argumentation systems exists, such as Defeasible Logic Programming (DeLP), specifying a knowledge representation language, and how arguments are built. In this work we combine time representation capabilities of TAF with the representation language and argument structure of DeLP, deﬁning a rule-based argumentation framework that considers time at the object language level. In order to do this, we use an extension of DeLP, called Labeled DeLP (l-DeLP) to establish, for each program clause, the set of time intervals in which it is available, and to determine from this information the temporal availability of arguments. Acceptability semantics for TAF can then be applied to determine argument acceptability on time